Research on real estate 3D modeling based on integration of physical entity and property entity - Zhang, Jiyi; Yang, Fan; Shi, Zhifeng; Zhang, Chi; Zhou, Liangchen (Frontiers in Earth Science, 2023)
The essence of three-dimensional (3D) real estate modeling is to build a 3D model that meets the requirements of the registration business in the information world according to the objective form of real estate objects and relevant legal provisions on real estate registration. It is the application of digital twin technologies in the field of real estate registration. In recent years, scholars have carried out much research and made a number of representative achievements in the field of 3D real estate modeling. Many countries and regions have started to implement 3D real estate registration. However, different countries have different legal provisions on real estate registration. Compared with other countries and regions in the world that have implemented 3D real estate registration, China’s 3D real estate registration is still in the exploratory stage. Although Chinese scholars have conducted much research from the perspectives of the 3D real estate registration mode, modeling method, legal framework, etc., existing studies mainly focus on the geometric modeling of physical entities and ignore the research on integrated modeling of physical entities and property right entities of real estate objects. Meanwhile, existing research results lack a combination with real estate registration practice. This research is one of the core contents of the pilot construction of Xinyi City’s two-dimensional (2D) and 3D integrated real estate electronic license registration. Combined with the real estate registration business practice in Xinyi City, this paper has developed a multilevel 3D real estate property rights modeling technology that integrates the physical entities and property right entities of the real estate registration object. The research results were applied to the real estate registration management of Xinyi City, supporting the issuance of the first 2D and 3D integrated real estate registration electronic license in Jiangsu.